KEGAGALAN HUKUM DI INDONESIA DALAM MENCIPTAKAN KEPASTIAN HUKUM TERKAIT SENGKETA KEPAILITAN PERBANKAN SYARIAH - Yudha Indrapraja (Asy-Syari'ah, 2015)
The growth of Islamic Bank in Indonesia can lead to potential disputes between the customer and the Islamic bank. In this case, there was regulation in Islamic Banking as well as to govern Islamic Banking disputes that was in Sharia Banking Law Number 21 of 2008. Unfortunately the explanation of Article 55 of this Act has caused by legal uncertainty that is given by the presence of two authorized judiciary in resolving disputes in Islamic Banking litigation. However,  Panel of Judges of the Constitutional Court in its Decision Nomor 93/PUU-X/2012 decided to entire Islamic Banking Dispute Resolution into religious court jurisdiction. In reality, not all Islamic Banking Dispute Resolution into religious court jurisdiction. Islamic Banking Bankruptcy Disputes are still handled by the Commercial Court, which are located within the General Court.  This paper will provide an overview of Islamic Banking Dispute Resolution before and after the Sharia Banking Law Number 21 of 2008, general description of the decision of the Constitutional Court, the Islamic Banking Dispute Resolution after the issuance of the decision of the constitutional court, and the Islamic Banking Bankruptcy Dispute Resolution before and after decision the Constitutional Court.